2009
DOI: 10.1051/0004-6361/200810296
|View full text |Cite
|
Sign up to set email alerts
|

2D non-LTE radiative modelling of He I spectral lines formed in solar prominences

Abstract: Context. The interpretation of high-resolution spectropolarimetric observations of solar prominences completed primarily at visible and near-infrared wavelengths, requires radiative modelling that takes into account both multi-dimensional geometry and complex atomic models.Aims. We enhance the interpretation of observations of He i multiplets, by considering 2D non-LTE unpolarized radiation transfer, and taking into account of the atomic fine-structure of helium. Methods. We apply our 2D non-LTE radiative tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The optical thinness of prominence plasma in He i D3 has been documented convincingly by i) the semi-empirical modeling of He i D3 profiles (Landman, Edberg, and Laney, 1977;Fontenla, 1979;Landman, 1981;Li, Gu, and Chen, 2000), ii) the non-LTE radiative modeling of He i D3 Gouttebroze, 2001, 2004;Léger, 2008;Léger and Paletou, 2009), and iii) the obvious observational fact of the on-disk transparency of filaments in He i D3. The non-local thermal equilibrium (non-LTE) 2D multi-thread modeling by Léger (2008) and Léger and Paletou (2009) showed that under realistic conditions the prominence plasma never becomes optically thick for He i D3.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…The optical thinness of prominence plasma in He i D3 has been documented convincingly by i) the semi-empirical modeling of He i D3 profiles (Landman, Edberg, and Laney, 1977;Fontenla, 1979;Landman, 1981;Li, Gu, and Chen, 2000), ii) the non-LTE radiative modeling of He i D3 Gouttebroze, 2001, 2004;Léger, 2008;Léger and Paletou, 2009), and iii) the obvious observational fact of the on-disk transparency of filaments in He i D3. The non-local thermal equilibrium (non-LTE) 2D multi-thread modeling by Léger (2008) and Léger and Paletou (2009) showed that under realistic conditions the prominence plasma never becomes optically thick for He i D3.…”
Section: Introductionmentioning
confidence: 91%
“…Gouttebroze, Heinzel, and Vial, 1993;Léger and Paletou, 2009). Figure 10 displays the typical and average He i D3 profiles free of the instrumental smearing by the gray circles and their multi-Gaussian fits, comprising the cool (thin blue and red lines) and hot components (thick lines), shown by the black lines.…”
Section: Multi-gaussian Modelmentioning
confidence: 99%
See 3 more Smart Citations